2015
DOI: 10.1155/2015/302820
|View full text |Cite
|
Sign up to set email alerts
|

Improving Osteogenesis Activity on BMP-2-Immobilized PCL Fibers Modified by theγ-Ray Irradiation Technique

Abstract: The purpose of this study was to demonstrate the ability of BMP-2-immobilized polycaprolactone (PCL) fibers modified using the γ-ray irradiation technique to induce the osteogenic differentiation of MG-63 cells. Poly acrylic acid (AAc) was grafted onto the PCL fibers by the γ-ray irradiation technique. BMP-2 was then subsequently immobilized onto the AAc-PCL fibers (BMP-2/AAc-PCL). PCL and surface-modified PCL fibers was characterized by evaluation with a scanning electron microscope (SEM), X-ray photoelectron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Water contact angle was also noticeably decreased, with lowered hydrophobicity of scaffolds possibly playing into increased osteogenic differentiation of cells on PCL/HA-3d scaffolds. Consistently, more intense cytoskeletal staining was observed on the HA-modified scaffolds, suggesting stronger cell attachment on PCL/HA-3D scaffolds possibly contribute to the improved osteogenic differentiation as well [34, 35].…”
Section: Discussionmentioning
confidence: 85%
“…Water contact angle was also noticeably decreased, with lowered hydrophobicity of scaffolds possibly playing into increased osteogenic differentiation of cells on PCL/HA-3d scaffolds. Consistently, more intense cytoskeletal staining was observed on the HA-modified scaffolds, suggesting stronger cell attachment on PCL/HA-3D scaffolds possibly contribute to the improved osteogenic differentiation as well [34, 35].…”
Section: Discussionmentioning
confidence: 85%
“…Kim et al [ 34 ] observed that the release of BMP-2 from their PCL-based scaffold resulted in a remarkable increase in new bone formation. Lee et al [ 35 ] and Yun et al [ 36 ] have shown that the release of BMP-2 leads to an increase in alkaline phosphatase (ALP) activity, ALP being an early osteogenic marker. The release of BMP-2 by their PCL scaffold promotes the differentiation of cells into bone lineage cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that BMP-2 was successfully immobilized onto the surface of PCL/ P3ANA nanofibers. 24…”
Section: Characterization Of Bmp-2 Immobilized Pcl/p3ana Nanofibersmentioning
confidence: 99%
“…3,19,22,23 Carboxylic acid groups of P3ANA not only provide active sides for covalent BMP-2 immobilization onto the nanofibers but also result hydrophilic surface which enhances the cellnanofiber interactions. 24 PCL which is a biocompatible and biodegradable polymer was used to obtain electrospun nanofibers of P3ANA. 25 PCL have been used especially in bone tissue engineering due to its slow degradation nature.…”
Section: Introductionmentioning
confidence: 99%